Bioindicadores de Flora y Fauna Silvestre como Servicios Ecosistémicos en Concesión Forestal, Madre de Dios - Magán Roeder, Julio Enrique (2025)
This study was carried out in the Loretillo forest concession (No. 17-TAM/C-OPB-A-026-07), located in the Las Piedras River conservation corridor in Tambopata, Madre de Dios. The main objective was to conduct an inventory of wildlife species, focusing on their use as bioindicators of the ecosystems within the concession. The study considered variables such as the species composition of flora, birds, and mammals, as well as the ecosystem services they provide (ESS). To this end, eight Permanent Sampling Plots (PSPs) and linear transects were established, distributed across two predominant ecosystem types: alluvial flooded forest (B-ai) and lowland hill forest (B-cb). The analyses included alpha and beta diversity indices, ecological importance values ​​(IVI), and parameters related to threatened species. The B-ai ecosystem was found to have greater biological richness and diversity. The assessment was based on criteria such as species richness (S), dominance (D), IVI, distribution breadth, conservation objectives, and threat categories. 48 bioindicator species were identified: 20 plant species, 17 bird species, and 11 mammal species, for both ecosystem types. From these species, the main ecosystem services they provide were determined, highlighting the regulation service (including climate regulation, pollination, seed dispersal, and biological control). Likewise, the ecological functionality of bioindicators was characterized in relation to their role within the trophic structure. The identification of these bioindicators and their ecosystem services provides a fundamental basis for establishing strategies for conservation, monitoring, and sustainable forest management. Furthermore, it promotes alternatives such as ecosystem service compensation mechanisms, contributing to the maintenance of biodiversity in the region.